Effect of iron supplementation on incidence of infectious illness in children: systematic review. Issue 7373 (16th November 2002) - Gera, Tarun; Sachdev, H P S
Abstract: Objective :To evaluate the effect of iron supplementation on the incidence of infections in children. Design : Systematic review of randomised controlled trials. Data sources :28 randomised controlled trials (six unpublished and 22 published) on 7892 children. Interventions : Oral or parenteral iron supplementation or fortified formula milk or cereals. Outcomes :Incidence of all recorded infectious illnesses, and individual illnesses, including respiratory tract infection, diarrhoea, malaria, other infections, and prevalence of positive smear results for malaria. Results : The pooled estimate (random effects model) of the incidence rate ratio (iron v placebo) was 1.02 (95% confidence interval 0.96 to 1.08, P=0.54; P<0.0001 for heterogeneity). The incidence rate difference (iron minus placebo) for all recorded illnesses was 0.06 episodes/child year (−0.06 to 0.18, P=0.34; P<0.0001 for heterogeneity). However, there was an increase in the risk of developing diarrhoea (incidence rate ratio 1.11, 1.01 to 1.23, P=0.04), but this would not have an overall important on public health (incidence rate difference 0.05 episodes/child year, −0.03 to 0.13; P=0.21). The occurrence of other illnesses and positive results on malaria smears (adjusted for positive smears at baseline) were not significantly affected by iron administration. On meta-regression, the statistical heterogeneity could not be explained by the variables studied. Conclusion :Iron supplementation has no apparent harmful effect on the overall incidence of infectious illnesses in children, though it slightly increases the risk of developing diarrhoea.